The meaning of recovery in a regional mental health service: an action research study. (5th July 2014) - Kidd, Susan; Kenny, Amanda; McKinstry, Carol
Abstract Aim To explore the meaning of the term recovery to people with experience providing and receiving mental health services. Background Internationally, governments have proposed recovery‐oriented mental health policy. In practice, people managing mental health difficulties struggle to recover, self‐manage, or improve their quality of life. Mental health services increasingly provide acutely focused and poorly coordinated services to people experiencing mental health difficulties, with self‐management, wellness and recovery overlooked. Design A cooperative enquiry, action research design guided the study. Participants were people with experience of mental health difficulties from consumer, carer and clinician perspectives. Method Data were collected between August 2012–July 2013. Analysis was conducted using an iterative process for the duration of the study. A thematic network was developed that reflected key organizing themes. Results The overarching theme developed from the participants' group discussions, reflections, actions and observations was recovery as an ongoing quest in life. This global theme was constructed from five organizing themes: 'finding meaning', 'an invisible disability', 'empowerment and agency' 'connection' and 'the passage of time'. Conclusion Participatory approaches support the inclusion of lived experience perspectives. Structured processes are needed to bring different perspectives together to find solutions, through dialogue, and acknowledge the barriers to participation that people who use mental health services experience. The lack of integration of lived experience perspectives demonstrates forms of discrimination that inhibit consumer participation and prevent the recovery‐oriented transformation required in mental health systems.